2012
DOI: 10.12693/aphyspola.122.370
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Phase Diagram of a Liquid Crystal with 4-[2-(3-Fluorophenyl)ethyl]biphenyl Core of Molecules

Abstract: Basing on the results of dierential scanning calorimetry and transmitted light intensity methods and texture observations in the temperature range from −50 • C to 90 • C phase diagram of 1-[3-uoro-4-(1-methylheptyloxycarbonyl)phenyl]-2-[4 ′-(2,2,3,3,4,4,4-heptauorobutoxybutoxy)biphenyl-4-yl]ethane was established. Monotropic system of thermodynamic phases was found. On cooling the isotropic phase transforms at 85 • C to ferroelectric SmC * phase and further two liquid crystalline phases, antiferroelectric SmC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…7−9 It is especially true for glass-formers, where the phenomenon of the so-called cold crystallization (cc) occurs on heating a substance. 10−14 For low molecular organic materials, the cc (a process typical for polymers and called recrystallization) has been identified on heating after softening of glasses of isotropic phases, 12−14 nematics, 7,15,16 crystal-like smectics, [7][8][9][10]17 conformationally disordered crystalline phases, 10,18 and ferroelectric phases 9,19 of liquid crystalline materials and also of plastic phases of alcohols. 20,21 In many cases, a metastable crystal is formed (one or more) which transforms on further heating to the stable crystalline phase.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7−9 It is especially true for glass-formers, where the phenomenon of the so-called cold crystallization (cc) occurs on heating a substance. 10−14 For low molecular organic materials, the cc (a process typical for polymers and called recrystallization) has been identified on heating after softening of glasses of isotropic phases, 12−14 nematics, 7,15,16 crystal-like smectics, [7][8][9][10]17 conformationally disordered crystalline phases, 10,18 and ferroelectric phases 9,19 of liquid crystalline materials and also of plastic phases of alcohols. 20,21 In many cases, a metastable crystal is formed (one or more) which transforms on further heating to the stable crystalline phase.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Studies of phase transitions in liquid crystalline materials revealed complex polymorphism of liquid-like and solid-like phases. It is especially true for glass-formers, where the phenomenon of the so-called cold crystallization (cc) occurs on heating a substance. For low molecular organic materials, the cc (a process typical for polymers and called recrystallization) has been identified on heating after softening of glasses of isotropic phases, nematics, ,, crystal-like smectics, , conformationally disordered crystalline phases, , and ferroelectric phases , of liquid crystalline materials and also of plastic phases of alcohols. , In many cases, a metastable crystal is formed (one or more) which transforms on further heating to the stable crystalline phase. Research on the kinetics of cold-crystallization in liquid crystalline glass-formers was conducted by polarizing microscopy (POM) along with calorimetric (adiabatic and/or DSC) methods ,, and broadband dielectric spectroscopy (BDS), also performed in real time of the experiment. ,,, …”
Section: Introductionmentioning
confidence: 99%